2011
DOI: 10.1007/s00198-011-1702-2
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Liaison Services: the UK experience

Abstract: Fracture Liaison Services (FLS) have been shown to deliver clinically and cost-effective osteoporosis care for patients presenting to hospital with fragility fractures. During the first decade of the new millennium, a consensus emerged in the UK on the need for universal access to FLS. This presentation described constructive interactions between policy makers, professional organizations, patients and their associations, and pharmaceutical manufacturers that led to the incorporation of FLS into national policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 19 publications
(18 reference statements)
1
39
0
4
Order By: Relevance
“…A review of the Glasgow Osteoporosis and Falls Strategy reported that hip fracture rates in the city had reduced by 7.3% over the decade, compared with a 17% increase in fracture rates for the entire population of England over the same period. 19,24 These findings are consistent with observational data from the USA by Dell, who reported a 37.2% reduction in hip fracture rates. 25 However, the strongest evidence on effectiveness has recently been provided by an Australian study that was designed as a prospective observational trial with a concurrent control group in which, compared with standard care, targeted identification and management significantly reduced the risk of refracture by > 80%.…”
Section: Current Knowledgesupporting
confidence: 86%
See 3 more Smart Citations
“…A review of the Glasgow Osteoporosis and Falls Strategy reported that hip fracture rates in the city had reduced by 7.3% over the decade, compared with a 17% increase in fracture rates for the entire population of England over the same period. 19,24 These findings are consistent with observational data from the USA by Dell, who reported a 37.2% reduction in hip fracture rates. 25 However, the strongest evidence on effectiveness has recently been provided by an Australian study that was designed as a prospective observational trial with a concurrent control group in which, compared with standard care, targeted identification and management significantly reduced the risk of refracture by > 80%.…”
Section: Current Knowledgesupporting
confidence: 86%
“…A fracture liaison service (FLS) is the recommended model proposed by the Department of Health to organise secondary fracture prevention services 1 in a 'one-stop shop' setting delivered by a nurse specialist supported by a lead clinician ('champion') in osteoporosis. 19 However, currently only 30% of hospitals in England have established a FLS. 17 A single model incorporating all components of secondary fracture prevention has not been mandated.…”
Section: Current Guidelines In Fracture Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such data would aid decision makers implement policy decisions at a local and national level. A potential costeffective approach is through the implementation of coordinated approaches to fracture prevention such as fracture liaison services (FLS) [23,24]. The Glasgow Fracture Liaison Service [25] reported that for every 1000 patients with a fragility fracture assessed by FLS, 18 fragility fractures (including 11 hip fractures) were prevented.…”
Section: Discussionmentioning
confidence: 99%